Unilateral Ovarian Abscess Caused by Salmonella - Toshimitsu Tohya; Toshihiro Yoshimura; Chikashi Onoda (Hindawi Limited, 2003)
Background: Patients with unilateral ovarian abscesses due to Salmonella are rare.